ATR inhibition potentiates the radiation induced inflammatory tumor microenvironment - Dillon, Magnus T. (Clin Cancer Res, 2019)
PURPOSE: ATR inhibitors (ATRi) are in early phase clinical trials and have been shown to sensitise to chemotherapy and radiotherapy preclinically. Limited data have been published about the effect of these drugs on the tumor microenvironment. EXPERIMENTAL DESIGN: We used an immunocompetent mouse model of HPV-driven malignancies to investigate the ATR inhibitor AZD6738 in combination with fractionated radiation (RT). Gene expression analysis and flow cytometry were performed post-therapy. RESULTS: Significant radiosensitization to RT by ATRi was observed alongside a marked increase in immune cell infiltration. We identified increased numbers of CD3+ and NK cells but most of this infiltrate was composed of myeloid cells. ATRi plus radiation produced a gene expression signature matching a type I/II interferon response with upregulation of genes playing a role in nucleic acid sensing. Increased MHC I levels were observed on tumor cells, with transcript-level data indicating increased antigen processing and presentation within the tumor. Significant modulation of cytokine gene expression (particularly CCL2, CCL5 and CXCL10) was found in vivo, with in vitro data indicating CCL3, CCL5 and CXCL10 are produced from tumor cells after ATRi + RT. CONCLUSIONS: We show that DNA damage by ATRi and RT leads to an interferon response through activation of nucleic acid sensing pathways. This triggers increased antigen presentation and innate immune cell infiltration. Further understanding of the effect of this combination on the immune response may allow modulation of these effects to maximise tumor control through anti-tumor immunity.